2007
DOI: 10.1097/grf.0b013e31804c9f05
|View full text |Cite
|
Sign up to set email alerts
|

Should We Treat Periodontal Disease During Gestation to Improve Pregnancy Outcomes?

Abstract: Until recently many physicians in the United States including obstetrician gynecologists have been relatively unconcerned with oral health. During most physical examinations, the oral cavity is given only a rudimentary examination. With the recognition of the oral-systemic health care link, physicians have been keenly interested in the findings from their dental colleagues in periodontal medicine which have convincingly linked periodontal disease with such diverse systemic health complications as aging, Alzhei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
9
0
2
Order By: Relevance
“…Although some of the bacteria in these biofilms are more pathogenic than others, periodontal diseases are diverse polymicrobial infections caused by a complex consortium of bacteria. They are not simply caused by anaerobic gram-negative rods and spirochetes as implied by some authors (20,21,60,180).…”
Section: Effects Of Pregnancy On Plaqueinduced Periodontal Infectionsmentioning
confidence: 90%
“…Although some of the bacteria in these biofilms are more pathogenic than others, periodontal diseases are diverse polymicrobial infections caused by a complex consortium of bacteria. They are not simply caused by anaerobic gram-negative rods and spirochetes as implied by some authors (20,21,60,180).…”
Section: Effects Of Pregnancy On Plaqueinduced Periodontal Infectionsmentioning
confidence: 90%
“…[4][5][6][7][8][9] Some authors proposed that periodontitis may not be causally related to negative birth outcomes and that both may result from the same hyperinflammatory and/ or environmental influences in the mothers. 10,11 Gram-negative periodontal pathogens and their products (e.g., lipopolysaccharides [LPS]) have been shown to enter the systemic circulation and produce low-grade bacteremia, 12 which may translocate to the placenta or uterus and impair birth outcomes. [13][14][15][16][17] Leó n et al 18 found Porphyromonas gingivalis in the amniotic fluid of postpartum females with PB and intact membranes.…”
Section: Introductionmentioning
confidence: 99%
“…However, contradictory results were reported by six meta‐analyses on the association between maternal periodontal disease and the risk of PB and/or LBW 4‐9 . Some authors proposed that periodontitis may not be causally related to negative birth outcomes and that both may result from the same hyperinflammatory and/or environmental influences in the mothers 10,11 . Gram‐negative periodontal pathogens and their products (e.g., lipopolysaccharides [LPS]) have been shown to enter the systemic circulation and produce low‐grade bacteremia, 12 which may translocate to the placenta or uterus and impair birth outcomes 13‐17 .…”
mentioning
confidence: 99%
“…Deux à quatre jours après l'accouchement, les femmes ont eu un examen parodontal dans leur chambre en suites de couches, en aveugle de la cause de prématurité. L'examen a été réalisé avec une sonde parodontale manuelle (PCPUNC-15 Hu-Friedy ® ), sur 6 sites par dent, sur les 14 dents les plus fréquemment touchées par la parodontite (11,12,16,17,24 [8,38,41]. Parodontite et prééclampsie pourraient partager des facteurs de risque communs et refléter une certaine susceptibilité aux pathologies inflammatoires.…”
Section: Méthodesunclassified